2D, 3D or speech? A case study on which user interface is preferable for what kind of object interaction in immersive virtual reality. (August 2019) - Hepperle, Daniel; Weiß, Yannick; Siess, Andreas; Wölfel, Matthias
Highlights: Participants experienced the 3D Interface to be the most fun. The Speech Interface is the fastest, most efficient and simplest interface. Steps/Task via Speech Interface significantly relate to the experience of the app. The 2D Interface offers the best overview. Offers an overview of which interface to use for a respective task. Graphical abstract: Abstract: Recent developments in human machine interaction offer three principal different approaches to interact with 3D environments, namely: 2D overlays using icons, 3D interfaces resembling interactions of the real world and speech interfaces which matured in the last years and are becoming more and more popular in other context such as smartphones or smart homes. Faced with the task to select the best interaction strategy to interact with immersive environments one is left with best practice and literature. But neither offers a clear strategy and all the methods are used widely. In particular a consistent comparison providing insights on when to use what interface in immersive virtual environments is missing. In order to evaluate the relative strengths and weaknesses of each interface in relation to different tasks in immersive environments a quantitative user study has been conducted. Results showed significant differences on the interface performances according to different parameters: ease of learning (Speech and 2D are favored), uncomplicated handling (Speech), speed (Speech and 2D), overview (2D), fun (3D), comprehension (2D and 3D) and on how simple and efficient it is to handle text input (Speech).